Summertime dropouts [videorecording (DVD)] - Torabpour, Hamid R.; Torabpour, Mamille; Chase, Jhene; Podany, Nicholas; Lloyd, Takaya Abdou; Evans, Crystal Lake; Donahoe, Caleb; Brook, Melanie; Laurel, Serena (Lionsgate, 2022)
Featuring music and an appearance from legendary rockers Simple Plan, here's a high-energy blast of fun the whole family can jam out to. Dave and his pop-punk band Summertime Dropouts are clean-cut, straight-edge kids looking for their big break. At a battle of the bands, Dave runs into his old high school crush Amy, and her rockin' trio. Will Dave and Amy get to play in the must-see music tour hitting the town? Will they finally get together? It's time to find out' and rock out.